Improving the design of a residential building using the SBToolPT methodology : a case study - Bragança, L. (2011)
This research work aims to assess the cost implications of improving the life-cycle sustainability of a residential building. For this purpose, a multifamily cooperative housing building block, that is the Portuguese pilot-project of the EU Project “SHE: Sustainable Housing in Europe”, has been chosen. This work will compare the sustainability of the case study with the conventional design approach in Portugal, i.e. when the conventional technologies and building materials are used. For this outcome the building sustainability assessment methodology SBToolPT - H will be used. This paper will highlight the usefulness of a building sustainability assessment tool in supporting and recognizing the sustainable building design. It will also show that even with little investment in the capital costs it is possible to archive high performance residential buildings.